2020
DOI: 10.2147/ott.s238958
|View full text |Cite
|
Sign up to set email alerts
|

<p>Phillygenin, a MELK Inhibitor, Inhibits Cell Survival and Epithelial–Mesenchymal Transition in Pancreatic Cancer Cells</p>

Abstract: Introduction: Pancreatic cancer (PC) is one of the leading causes of cancer, with the lowest 5-year survival rate of all cancer types. Given the fast metastasis of PC and its resistance to surgery, radiotherapy, chemotherapy, and combinations thereof, it is imperative to develop more effective anti-PC drugs. Phillygenin (PHI) has been reported to exert anti-cancer, antibacterial, and anti-inflammatory properties. However, the mechanism of PHI in the development of PC is still unclear. Methods: The cytotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…EMT indicates a biological process in which the epithelial cells gain the properties of mesenchymal cells when cells undergo embryonic development or pathological processes [ 14 , 29 ]. During the EMT process, lots of alterations happen in cellular phenotypes and gene expressions.…”
Section: Discussionmentioning
confidence: 99%
“…EMT indicates a biological process in which the epithelial cells gain the properties of mesenchymal cells when cells undergo embryonic development or pathological processes [ 14 , 29 ]. During the EMT process, lots of alterations happen in cellular phenotypes and gene expressions.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that phillygenin is an important active ingredient of lignans with a fingerprint component in Forsythiae Fructus [ 4 ]. Furthermore, it is reported as a wide-used protector with various functions, such as antiviral, antioxidant, anti-inflammatory, anticancer, and antifibrosis effects [ 4 8 ]. MicroRNAs (miRs) are mainly negative regulators of their target genes through binding to 3'untranslated regions (3'UTRs) [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Toll-like receptor (TLR)4/MyD88/NF-κB signaling pathway, which can be activated by PHI, can inhibit lipopolysaccharide (LPS)-induced inflammation and further alleviate liver fibrosis (8). Furthermore, PHI has been reported to have significant antitumor effects in human esophageal and pancreatic cancer types (10,11).…”
Section: Introductionmentioning
confidence: 99%